2016
DOI: 10.1136/bmjopen-2015-010183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and age on the association between suicidal behaviour and obesity in Korean adults: a cross-sectional nationwide study

Abstract: ObjectivesTo examine the hypothesis that the relationship between obesity and the risk of suicidal behaviour would differ according to sex and age.SettingData from the 2007–2012 Korean National Health and Nutrition Examination Survey (KNHANES) were used.Participants36 211 adults with body mass index (BMI) data were included and the mean age was 49.6 years.Independent variableBMI.Primary and secondary outcome measuresSuicide ideation and attempts.Design and analysisA cross-sectional study was performed. Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Gao (2013) reported that the association between BMI and suicidality varied by gender and depression status, with an inverse relationship between BMI and suicide attempts among men regardless of depression history; and a curvilinear relationship among women, with higher incidence of attempts among low-BMI relative to normal weight women without history of depression, but a U-shared relationship among women with depression [ 19 ]. Kim et al (2016) also reported that the relationship between BMI and suicidality was curvilinear and varied by gender in a large sample of Korean middle-aged adults [ 37 ]. Results from studies of BMI and suicidality among adolescent or young adult samples have generally been smaller and results are mixed [ 25 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gao (2013) reported that the association between BMI and suicidality varied by gender and depression status, with an inverse relationship between BMI and suicide attempts among men regardless of depression history; and a curvilinear relationship among women, with higher incidence of attempts among low-BMI relative to normal weight women without history of depression, but a U-shared relationship among women with depression [ 19 ]. Kim et al (2016) also reported that the relationship between BMI and suicidality was curvilinear and varied by gender in a large sample of Korean middle-aged adults [ 37 ]. Results from studies of BMI and suicidality among adolescent or young adult samples have generally been smaller and results are mixed [ 25 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric information was collected by self-reported height and weight data. BMI was calculated therefrom, and participants were categorized according to criteria for Asians [35] or generally applied definitions for the Korean population [5, 36, 37] using BMI cut offs of <18.5 kg/m 2 (underweight), <23 kg/m 2 (normal), ≥23 kg/m 2 (overweight), and ≥25 kg/m 2 (obese).…”
Section: Methodsmentioning
confidence: 99%
“…In another cross-sectional study using the Korea National Health and Nutrition Examination Survey, the obese population was classified and analyzed by sex and age. There were many suicide attempts in severely obese women but the suicide attempts were higher for men when underweight, suggesting the possibility of a variable relationship between obesity and suicide according to sex and age [21]. However, as the number of studies on the relationship between obesity and suicide targeting Koreans are scarce, there are expected limitations in investigating clear correlations to clarify which results to generalize and apply.…”
Section: Discussionmentioning
confidence: 99%